A brief measure of hospital anxiety: design and preliminary psychometric analysis of a scale. - Basauri Delgado, Miguel Angel (2022)
Objective: Objective: To establish a preliminary psychometric analysis of a brief hospital anxiety scale. Method: Non-experimental study of instrumental design, with a unit of analysis of 60 participants, who were nurses and physicians from a hospital in Metropolitan Lima. Main results: The final version was reduced to 9 items, obtaining adequate evidence of content validity by the criterion of expert judges (V > .80). The evidence of construct validity showed a unidimensional model that explains 72.5% of the variance, with factor loadings greater than .30 (.773 to .939). The reliability found was for internal consistency with acceptable values (α=.958; ω=.959; θ=.957). General conclusion: The EAH-9 constitutes a preliminary alternative with evidence of validity and reliability for the analysis of anxiety in hospital professionals.